2023
DOI: 10.31004/basicedu.v7i1.4363
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Platform Merdeka Mengajar untuk Meningkatkan Kompetensi Guru di Sekolah Dasar

Abstract: Merdeka belajar merupakan inovasi dalam kebebasan dalam proses pembelajaran yang memberikan pengalaman belajar sesuai dengan kebutuhan dan krakteristik dari siswa. Dengan adanya aplikasi untuk belajar mandiri diharapkan setiap guru memiliki kompetensi Guru abad 21 yaitu  guru profesional yang bukan hanya sekedar pendidik yang bisa mengajar hanya dengan predikat baik. Melainkan pendidik yang bisa menjadi pembelajar dan agen perubahan sekolah, serta bisa menjalin dan mengembangkan hubungan untuk peningkatan mutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
30

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 9 publications
3
12
0
30
Order By: Relevance
“…That is, PMM has an impact not only on teachers but also on students. The results of this study are supported by several studies stating that the use of PMM can improve teacher competencies and help the learning process (Aulia et al, 2023;Defa et al, 2023;Marisana et al, 2023;Ramdani et al, 2022;Suryadi & Hidayati, 2023), including in mathematics learning (Budiarti, 2022). These research findings are also supported by the results of (Susanti et al, 2023;Triscova et al, 2022), who reported that teachers found it helpful in understanding the implementation of the Merdeka curriculum and were highly inspired in designing teaching modules and creative learning content.…”
Section: Learning Implementation Results Below Standardsupporting
confidence: 81%
See 1 more Smart Citation
“…That is, PMM has an impact not only on teachers but also on students. The results of this study are supported by several studies stating that the use of PMM can improve teacher competencies and help the learning process (Aulia et al, 2023;Defa et al, 2023;Marisana et al, 2023;Ramdani et al, 2022;Suryadi & Hidayati, 2023), including in mathematics learning (Budiarti, 2022). These research findings are also supported by the results of (Susanti et al, 2023;Triscova et al, 2022), who reported that teachers found it helpful in understanding the implementation of the Merdeka curriculum and were highly inspired in designing teaching modules and creative learning content.…”
Section: Learning Implementation Results Below Standardsupporting
confidence: 81%
“…That is, PMM has an impact not only on teachers but also on students. The results of this study are supported by several studies stating that the use of PMM can improve teacher competencies and help the learning process(Aulia et al, 2023;Defa et al, 2023;Marisana et al, 2023;Ramdani et al,…”
supporting
confidence: 81%
“…Kesibukan mengurus adminstrasi pembelajaran merupakan bagian dari proses pembelajaran. (Daga, 2021;Dasar et al, 2023;Rahayu, Rosita, Rahayuningsih, 2021). Kesibukan guru yang terjebak dalam administrasi pembelajaran sehingga guru menjadi tidak optimal dalam melaksanakan proses pembelajaran di kelas.…”
Section: Pendahuluanunclassified
“…Berbagai kegiatan sebagai upaya peningkatan mutu pendidikan di Indonesia telah dicoba/laksanakan berulang kali, di antaranya studi [7] yaitu bagi guru di Kabupaten Kendal diberikan pelatihan komprehensif berkenaan dengan penulisan dan penyuntingan artikel ilmiah, begitu juga [8] yang memberikan pelatihan melalui in-house training terkait proses belajar jarak jauh guna peningkatan kompetensi/kemampuan guru SMK [9], [10]. Terkait dengan upaya peningkatan kompetensi guru diantaranya telah dilakukan [11], [12], [13], [14], Sedangkan kegiatan pendampingan kepada guru terkait 10 Ayu Aulia Oktaviani, Moch. Sabur, Triyanto Peningkatan kompetensi penyusunan jurnal dan buku besar bagi anggota P2KPTK2 Jakarta Barat upaya peningkatan kemampuan guru [7], begitupun yang memberikan upaya pendampingan guru untuk Optimalisasi Pembelajaran [15].…”
Section: Pendahuluanunclassified